RANCANG BANGUN SISTEM PELAYANAN HOME SERVICE PADA YOYENA OPTIC BERBASIS WEB - yoga firstma heranda; Siti Nurmiati (JURNAL REKAYASA INFORMASI, 2021)
This research is motivated by the condition of Indonesian people who are still averse to eye health. Optic as a provider of public health services has not been utilized optimally. Covid-19 pandemic in Indonesia causing the worse condition and impacting optic service providers. People are increasingly reluctant to check their eyes health, because it is difficult to get services from optic as a provider. The research titled: "Designing an Optic’s Home Service System Based on Web" discusses what factors are causing Indonesians to be reluctant to check their eyes. In addition, this research will produce an application system designed with modeling language using UML. So, the user can easily check their eyes. While, the program used by the researcher is PHP with MySQL database. The main purpose of this research is to facilitate consumers in obtaining eye health checking services through a website and application. So that between consumers and service providers mutually beneficial to each other. Consumers get the ease of obtaining services, while the service providers can easily serve consumers more effectively. The end result of this research is the creation of an application system that utilizes home service. Keywords: Eye Health, Service, Optic, Home Service